Smart H2S‐Triggered/Therapeutic System (SHTS)‐Based Nanomedicine - Chen, Weiyu; Ni, Dalong; Rosenkrans, Zachary T.; Cao, Tianye; Cai, Weibo (Advanced science, 2019)
Hydrogen sulfide (H2S) is of vital importance in several biological and physical processes. The significance of H2S‐specific detection and monitoring is emphasized by its elevated levels in various diseases such as cancer. Nanotechnology enhances the performance of chemical sensing nanoprobes due to the enhanced efficiency and sensitivity. Recently, extensive research efforts have been dedicated to developing novel smart H2S‐triggered/therapeutic system (SHTS) nanoplatforms for H2S‐activated sensing, imaging, and therapy. Herein, the latest SHTS‐based nanomaterials are summarized and discussed in detail. In addition, therapeutic strategies mediated by endogenous H2S as a trigger or exogenous H2S delivery are also included. A comprehensive understanding of the current status of SHTS‐based strategies will greatly facilitate innovation in this field. Lastly, the challenges and key issues related to the design and development of SHTS‐based nanomaterials (e.g., morphology, surface modification, therapeutic strategies, appropriate application, and selection of nanomaterials) are outlined. H2S‐specific nanoagents are of vital importance in detecting endogenous and exogenous H2S gas. The recent developments of these smart H2S‐triggered/therapeutic systems (SHTSs) are summarized. Additionally, the challenge faced, and the principals involved, are further discussed for future H2S‐nanoprobe designs.